Film Animasi Wayang Beber "SAYEMBARA KEDIRI” FILM ANIMASI DUA DIMENSI DENGAN KONSEP REINTERPRETASI TERHADAP WAYANG BEBER PACITAN: "SAYEMBARA KEDIRI” FILM ANIMASI DUA DIMENSI DENGAN KONSEP REINTERPRETASI TERHADAP WAYANG BEBER PACITAN - Fajar, Fajar Abadi; Munir, Moch. Syahrul; Prameswari, Citra Ratih (Journal of Electrical, Electronic, Mechanical, Informatic and Social Applied Science, 2023)
The animated film Wayang Beber Contest Kediri as an effort to increase public awareness, especially the younger generation, in caring for and maintaining the noble cultural tradition in order to remain sustainable. The publication media chosen is 2D Short Animated Film, because animation is an interesting medium and can be seen by all ages. The creation of the animated film "Sayembara Kediri" with the Two-Dimensional Technique uses the experimental method. The process of making Wayang Beber animation "Sayembara Kediri", namely: starting from the pre-production, production and post-production processes. The structure or personal technique in the creation of the Wayang Beber Animated Film “Sayembara Kediri” is; 1. Experiment (Media Research), 2. Contemplation (Inner Research); and Formation. The work of the Wayang Beber animation film needs to be of great interest to the public, especially the younger generation, so that they are able to become entrances in inculcating noble values and strengthening national identity and cultural resilience Keywords: 2D Animation, Wayang Beber, Kediri Contest